WOMEN'S LANGUAGE FEATURES OF EILIS LACEY IN THE BROOKLYN MOVIE SCRIP - Sekar Lantik Pamikat (UC Journal: ELT, Linguistics and Literature Journal, 2020)
This paper analyzed womens language features used by Eilis Lacey in the Brooklyn movie script. Brooklyn tells about Eilis Lacey, a pretty young woman who moved from Ireland to Brooklyn. Two research problems were formulated. First, what are the kinds of womens language features of Eilis Lacey in the Brooklyn movie script? Second, what are the uses of womens language features of Eilis Lacey in the Brooklyn movie script? In order to answer those two research questions, the researcher applied the theory of Lakoff (1975) on womens language. This research used a descriptive qualitative method that supported by quantitative method. The researcher described the data in sentences and tables and then counted the percentage shown in tables and diagrams. The researcher was the main instrument to collect the data needed. The data was taken from sentences used by Eilis Lacey in the Brooklyn movie script written by Nick Hornby. The researcher discovered that Eilis Lacey showed her femininity side in her using of womens language features related on Lakoffs theory when she was talking with her fiance, family, and friends. There were nine womens language features that she used, they were lexical hedges or fillers, tag questions, rising intonation on declaratives, intensifiers, super polite forms, emphatic stress, empty adjectives, precise color terms, and hypercorrect grammar.